Histone Deacetylation Regulated by KDM1A to Suppress DACT1 in Proliferation and Migration of Cervical Cancer - Lingjuan Zeng; Chunyan Chen; Chanjiao Yao (Analytical Cellular Pathology)
Objective. Increased expression of KDM1A and decreased expression of DACT1 in cervical cancer cells were noticed in a previous study. This study is aimed at exploring the mechanism behind the KDM1A regulation on DACT1 in cervical cancer cells. Methods. The expression profile of KDM1A and DACT1 in cervical cancer tissues was searched in TCGA database. In vitro experiments verified the effect of KDM1A and DACT1 on proliferation and migration ability of cervical cancer cell lines after cell transfection. The interaction of KDM1A with HDAC1 was identified by coimmunoprecipitation (Co-IP). The expression levels of KDM1A and DACT1 in cervical cancer cell lines were determined by qRT-PCR and western blot. Results. TCGA database showed that cervical cancer tissues had elevated expression of KDM1A and decreased expression of DACT1, which was consistent with the observation in cervical cancer cell lines. KDM1A was found to negatively regulate DACT1 through histone deacetylation. Meanwhile, the downregulation of KDM1A or overexpression of DACT1 could suppress the cell proliferation and migration ability in HeLa and SiHa cells. Cotransfection of KDM1A and DACT1 overexpression could reverse the increased cell proliferation and migration ability induced by KDM1A overexpression. Conclusion. KDM1A can downregulate DACT1 expression through histone deacetylation and therefore suppress the proliferation and migration of cervical cancer cells.